THE ASSESS OF DENTAL STUDENTS` KNOWLEDGE AND SKILLS IN MANAGEMENT OF MEDICAL EMERGENCIES IN DENTAL OFFICE - Iliyana Stoeva (Peytchinski Publishing, 2011)
Medical emergencies can occur in the dental office. The dental practitioner must be able to react immediately and adequately. The aim of the study was to investigate the knowledge and skills of dental students to react in medical emergency.Material and methods: A total of 136 dental students were inquired about the clinical symptoms and management in emergency situations.Results: With regard to theoretical preparation in emergency situations 72.8% of the students assess the dental education as excellent, 11.8% of the students assess their knowledge as satisfactory and 15.4% of the dental students find difficulties to differentiate the emergency situations. No one of the students is feeling able to manage in those situations. Conclusions: An urgent regulation to update the dental education programs is necessary.